EMBRYONIC AND EARLY LARVAE DEVELOPMENT OF WILD BETTA (Betta imbellis LADIGES 1975) - Sawung Cindelaras; Anjang Bangun Prasetio; Eni Kusrini (Pusbindiklat - LIPI, 2015)
Cupang (Betta imbellis) is a popular ornamental and fighting fish in Indonesia. Its popularity is not followed by its scientific information. The aim of this study was to explore the embryonic stages and early larva development. This information is needed for fish breeding. Total of 20–40 eggs and larvae were observed under a microscope with 40 and 100 magnifications. Eggs were observed every cleavage stage and larvae were observed every 12 hours. Fertilized eggs were seen translucent with dark yolk egg in a diameter of 1.09±0.04 mm. Cleavage stages occurred during 4–55 minutes after fertilization. Larvae hatched ±29 hrs after fertilization.The length of hatched larvae was 2.42 ±0.076 m, while yolk volume was 0.11 ±0.028 mm2. Larvae became free-swimming in 2-3 days and yolk were fully absorbed in 3–4 days after hatching and started to eat. The cleavage stage occurs for 55 minutes after fertilization and becomes foraging with a size of mouth opening 0.31±0.005mm which could consume nauplii ofArtemiasp.